Fishes from lakes and tributaries of the rio santa bárbara, sapucaí-mirim/grande hydrographic basin, são paulo, brazil - Diniz, Paulo Baltazar [UNESP]; Siqueira, Hatus de Oliveira [UNESP]; Faleiros, Tâmer de Oliveira [UNESP]; Pereira, Nycolas Levy; Senhorini, José Augusto [UNESP]; Esguícero, André Luiz Henríques; Bertelli, Célio (Pensoft Publishers, 2019)
Rio Santa Bárbara, a small tributary of the Rio Sapucaí-Mirim, has undergone severe human intervention over the past 80 years. We surveyed the ichthyofauna of this river, some surrounding lakes, and the Rio Potreiro, a tributary. Four campaigns were carried out, 2 in the dry season and 2 in the rainy season. We found 920 specimens at 12 sites and included 32 species belonging to 6 orders and 16 families. The order Characiformes was found to be best represented in our study, followed by the orders Cichliformes and Siluriformes. The family Characidae was the most numerous, followed by the families Cichlidae and Poeciliidae. A specimen of Brycon nattereri was collected from the Rio Santa Bárbara; this species is Critically Endangered in the state of São Paulo.
Keywords: Conservation; Freshwater fishes; Neotropical biodiversity; Upper Rio Paraná